Automatic irrigation system with rain fall detection in agricultural field. (May 2020) - Barkunan, S.R.; Bhanumathi, V.; Balakrishnan, V.
Highlights: Efficient prototype model for the irrigation system by detecting rain fall. Rainfall, temperature, humidity and soil moisture are used to control the motor. Periodically updating the environmental status to the farmer through mobile phone. Amount of water utilization is less compared to existing traditional methods. Abstract: Rainfall is an important natural phenomenon for agricultural activities to fulfill its water requirements. The proposed irrigation technique in agriculture saves water by making it as an automated one. By detecting the rain fall in real time, the amount of water needed for the field can be planned. A system is developed based on ARM micro controller combined with GSM module to inform the rain fall level to the farmer and as well as automatically regulates the water irrigation. The system can monitor the current state of the land and data is transmitted to the mobile. The results obtained from the prototype are compared with the actual data taken from the web and it is found that the difference in estimation is minimum. The results from the prototype are compared with the traditional systems and it is found that the automation reveals best results in terms of water utilization.